Quelques remarques sur la genèse de la Chronique de Spišská Sobota - Adrien Quéret-Podesta (Medievalista)
The Chronicle of Spišská Sobota is a short historical text which owes its name to its place of conservation and relates the history of the German-speaking communities which settled in the Spiš region; however, rather little is known about the exact circumstances of its creation. The present paper aims to reconstitute the genesis of this work and proposes, despite its inevitably hypothetical and incomplete character, some directions of research. The analysis of the only preserved manuscript of the chronicle seems thus to show that this text was used as a tool of legitimation for the right of the Spiš German inhabitants, which suggests that the League of the Spiš towns could have been involved in the chronicle’s creation. The examination of the manuscript also seems to indicate that the chronicle was written at the turn of the 1450s and 1460s, i.e. only a few years before the end of the towns’ autonomy in 1465: the prospect of this event might thus have played a role in the creation of the chronicle. Finally, the analysis of place names in Spiš mentioned in this work strongly suggests it was composed in Levoča by one layman involved in the administration of the city.